2018
DOI: 10.1161/jaha.118.008657
|View full text |Cite
|
Sign up to set email alerts
|

Statins Reduce Abdominal Aortic Aneurysm Growth, Rupture, and Perioperative Mortality: A Systematic Review and Meta‐Analysis

Abstract: Background There are no recognized pharmacological treatments for abdominal aortic aneurysms ( AAA ), although statins are suggested to be beneficial. We sought to summarize the literature regarding the effects of statins on human AAA growth, rupture, and 30‐day mortality. Methods and Results We conducted a systematic review and meta‐analysis of randomized and observational studies using the Cochrane CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
77
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 83 publications
1
77
0
3
Order By: Relevance
“…40 In a clinical setting, a recent meta-analysis has stated that statin therapy may be associated with reduction in AAA progression, rupture, and lower rates of peri-operative mortality following elective AAA repair. 2 Also, in postdeployment of EVAR, it has been documented that statin therapy can be predictive of AAA sac diameter reduction. 41 Although optimisation with best medical treatment is recommended, evidence of the effect of single drugs has been conflicting 42 and further research is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 In a clinical setting, a recent meta-analysis has stated that statin therapy may be associated with reduction in AAA progression, rupture, and lower rates of peri-operative mortality following elective AAA repair. 2 Also, in postdeployment of EVAR, it has been documented that statin therapy can be predictive of AAA sac diameter reduction. 41 Although optimisation with best medical treatment is recommended, evidence of the effect of single drugs has been conflicting 42 and further research is required.…”
Section: Discussionmentioning
confidence: 99%
“…Later results, however, have shown that prophylactic treatment with statins should be included because of the effect on reduction in growth progression, rupture, and lower rates of peri-operative mortality. 2 Statins have also been shown to be independent predictors of decreased long term mortality after AAA. 3e7 The aim of the study was to search the literature to study the long term effects of statins after open surgical repair (OSR) and endovascular aneurysm repair (EVAR) in general and to search for possible trends in the choice of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Although recommended to reduce cardiovascular events (4), antiplatelet medications and antihypertensive agents have not been shown to influence AAA growth or rupture risk. Although a large systematic review found a possible association of statins with a reduction in AAA growth and rupture (114), similar effects have not been shown for other medication classes including angiotensin converting enzyme inhibitors, beta blockers, and doxycycline (41,58). Accordingly, screening for AAA in populations at risk (23), surveillance of small AAAs, and pre-emptive surgical repair at the point when risk of rupture outweighs the surgical risks are crucial.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent genetic studies suggest that lipids could play a role in the etiology of AAA [[7], [8], [9], [10]]. Similarly, the effect of statins on AAA displayed contradictory results, although more recent studies support a protective role of these drugs in preventing AAA growth and rupture [[11], [12], [13]]. Regardless of the potential contribution of lipids on AAA progression, it is well accepted that low levels of high-density lipoprotein (HDL) cholesterol are associated to both AAA presence and evolution [14,15].…”
Section: Introductionmentioning
confidence: 99%